Increased Plasma Levels of Free Tissue Factor Pathway Inhibitor in Patients with Graves’ Disease - Morishita, Eriko; Hashimoto, Takuma; Asakura, Hidesaku; Saito, Masanori; Yamazaki, Masahide; Aoshima, Keiji; Yoshida, Tomotaka; Kato, Hisao; Matsuda, Tamotsu (Thrombosis and Haemostasis, 1998)
Tissue factor pathway inhibitor (TFPI) is present in a free-form and in lipoprotein-associated forms in plasma. In this study, the plasma concentrations of total TFPI (tTFPI) and free-form TFPI (fTFPI) were measured in 25 patients with Graves’ disease and 25 age-matched healthy subjects, and the relationship between thyroid state and plasma TFPI was examined. Plasma concentrations (median) of tTFPI and fTFPI in Graves’ patients who were hyperthyroid were significantly increased compared with Graves’patients who were euthyroid (152 ng/ml versus 124 ng/ml, p <0.01 and 41.3 ng/ml versus 20.2 ng/ml, p <0.0001, respectively), and control subjects (152 ng/ml versus 96 ng/ml, p <0.0001 and 41.3 ng/ml versus 18.7 ng/ml, p <0.0001, respectively). There was no significant difference in plasma fTFPI concentrations between the euthyroid group and the control group. Plasma fTFPI concentrations correlated closely with thyroid hormone (T3) levels in the patients (r = 0.559, p <0.005). Serial measurement of individual patients revealed that plasma concentrations of fTFPI and tTFPI were significantly decreased, reaching normal control values upon attainment of euthyroidism. In conclusion, the close correlation between plasma fTFPI and serum thyroid hormone levels suggests that thyroid hormones might influence the synthesis or metabolism of TFPI on the surface of endothelial cells in patients with Graves’ disease. This is the first report concerning high concentrations of plasma fTFPI in patients with hyperthyroidism.